IMPACT OF DIGITAL MARKETING ON GENERATION Z CONSUMER BEHAVIOR IN UZBEKISTAN - Jaxongir Davronov Askarovich; Heny Hendrayati; Inomjon Qudratov (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
This study examines how digital marketing affects the consumer behavior and buying decisions of Generation Z in Uzbekistan. Using a Systematic Literature Review based on the PRISMA 2020 guidelines, peer-reviewed articles published from 2015 to 2024 were collected from Scopus, Web of Science, ScienceDirect, and Google Scholar. The review focuses on digital marketing, social media marketing, influencer marketing, and related behavioral responses among young consumers. The results show that visual and interactive online content has the strongest influence on Generation Z in Uzbekistan. Platforms like Instagram , TikTok, YouTube , and Telegram work best with short videos , content made by users , and recommendations from influencers . Young people are more likely to buy something from a brand if they trust it and believe it is real. People use social media a lot, but direct ads don't work as well as recommendations from friends and electronic word-of-mouth . Overall, digital marketing has a strong impact on the behavior of Generation Z consumers in Uzbekistan, and strategies focused on authenticity, cultural relevance, and meaningful engagement are more effective than intrusive advertising.